DETERMINANTS OF HIV INCIDENCE IN CHILDREN YEAR 2019 -2024 - Neila Sulung (Jurnal Endurance, 2025)
Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells, resulting in a weakened immune system. This makes individuals more susceptible to various infections. HIV remains a significant global public health issue, with an estimated 42.3 million deaths to date. Organizations such as WHO, Global Fund, and UNAIDS have aligned strategies aimed at eliminating the HIV epidemic by 2030, as part of SDG 3.3. This study employs a literature review methodology, using PRISMA and Quality Assessment techniques, focusing on research from 2019 to 2024. The findings highlight several key factors contributing to HIV in children, including vertical transmission, early diagnosis, socio-economic factors, the PMTCT program (Prevention of Mother-to-Child Transmission), and access to healthcare services. Barriers such as distance from healthcare facilities, limited resources, and logistical challenges affect HIV prevention and management in children. Vertical transmission from mother to child, which can occur during pregnancy, childbirth, or breastfeeding, remains the leading cause of HIV in children. A comprehensive approach, including medical interventions, increased awareness, and social support, is essential for significantly reducing HIV incidence in children. Keywords: determinant children, and HIV